2005
DOI: 10.1097/00008390-200512000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sentinel lymph node status and regression of primary malignant melanoma

Abstract: The prognostic significance of spontaneous regression of primary melanoma is a controversial issue. Studies on sentinel lymph node status and circulating tumour cells may represent a step towards a better understanding. The clinical details of 269 melanoma patients who underwent sentinel lymph node biopsy were analysed. Correlation was sought between the parameters of the primary tumour, particularly tumours showing a partial intermediate level of regression, and sentinel lymph node status. The presence of cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
2
17
0
2
Order By: Relevance
“…7,72,[74][75][76]78,[100][101][102][103] On the other hand, additional studies have suggested that regression indicates a favorable outcome (Table 3). 3,[104][105][106][107][108] Thus, the prognostic significance of regression in primary melanoma has been controversial for many years. In the next section, we discuss some of the most relevant published studies with respect to melanoma recurrence, lymph node metastasis, and survival.…”
Section: Prognostic Significance Of Regression In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…7,72,[74][75][76]78,[100][101][102][103] On the other hand, additional studies have suggested that regression indicates a favorable outcome (Table 3). 3,[104][105][106][107][108] Thus, the prognostic significance of regression in primary melanoma has been controversial for many years. In the next section, we discuss some of the most relevant published studies with respect to melanoma recurrence, lymph node metastasis, and survival.…”
Section: Prognostic Significance Of Regression In Melanomamentioning
confidence: 99%
“…2,4,7,76,82 Yet other studies have reported that the presence of regression may be associated with negative SLN status. 3,85,98,[105][106][107] Moreover, in a recent meta-analysis of 14 studies that included 10 098 patients with melanoma of various stages, Ribero et al 13 demonstrated that regression was associated with lower rates of SLN positivity.…”
Section: Association Between Regression and Recurrencementioning
confidence: 99%
“…Breslow thickness remains the most consistent predictor of sentinel lymph node metastases, but other parameters such as ulceration, age, location, angiolymphatic invasion, regression, small cell melanoma histology, and clinical tumor palpability may also be predictive. 15,19,[22][23][24][25][26][27][28][29][30][31][32][33][34] Tumor lymphangiogenesis is an active area of investigation in melanoma and other cancers and is postulated to be a fruitful area for therapeutic targets. 35 Excellent reviews are available discussing tumor lymphangiogenesis and melanoma metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos mostraram que MCFs com regressão representam um grupo com alto risco de metástases (4,7,13,14,26,28) ,enquanto outros não demonstraram relação entre estes fatores (12,19,20,21,27,32) . Também tem sido sugerido que tal influência negativa seria mais relevante entre os MCFs do que entre os melanomas espessos, sendo a regressão relacionada com alguns casos de metástases em melanomas in situ (MIS) (6,12,14) .…”
Section: Tabelaunclassified
“…Alguns autores mostraram aparente associação entre presença de regressão espontânea e comportamento biológico mais agressivo, com grande divergência nos resultados (12,19,20,21,27,32) . O que pode explicar tal divergência são as diferentes metodologias utilizadas.…”
Section: Regressão Como Fator Prognósticounclassified